Musculoskeletal disorders (MSD), stress, and elements of home environment among health sciences students in Malaysia / Erna Faryza Mohd Poot and Nor Ariani Nordin - Mohd Poot, Erna Faryza; Nordin, Nor Ariani (Faculty of Health Sciences, Universiti Teknologi MARA, 2022)
The COVID-19 pandemic has impacted Malaysia's education system where the learning medium shifted from face-to-face to online learning platforms. Consequently, it might impact students' stress levels and the prevalence of musculoskeletal disorders (MSD). In addition, the difference in home elements might influence the development of MSD. This study aimed to determine the prevalence of MSD and stress levels. Furthermore, to investigate the association between MSD with elements of the home environment. One hundred and thirty-six (n=130) health sciences students around Malaysia participated in this study. A cross-sectional study was carried out via an online survey using the Cornell Musculoskeletal Discomfort questionnaire (CMDQ) and Stress Student Inventory (SSI). More than 30% of participants reported the presence of MSD in almost all body parts. The majority of participants reported having mild stress (57.7%). The presence of MSD in 20 body parts showed a significant association (p<0.05) with physical, interpersonal relationships, academic, and environmental stress. Moreover, the presence of MSD in 7 body parts showed significant differences (p<0.05) with elements of the home environment. In conclusion, health sciences students have a high prevalence of MSD and the development of MSD was associated with stress and elements of the home environment.